A Malaysian Delphi consensus on managing knee osteoarthritis - Yeap, Swan Sim (BMC, 2021)
The 2013 Malaysian Clinical Practice Guidelines on the Management of Osteoarthritis (OA) recommend a linear step-up approach to manage knee OA. However, patients with knee OA often require a multimodal approach to address OA-related pain symptoms and functional limitations. This consensus aimed to provide doctors with an updated set of evidence-based, clinical experience-guided recommendations to manage knee OA.MethodsA multi-speciality expert panel consisting of nine Malaysian physicians from different healthcare settings who manage a diverse OA patient population was convened. Using a combination of the ADAPTE process and modified Delphi method, the panel reviewed current evidence on the management of knee OA and synthesised a set of nine recommendations on the management of knee OA, supported by an algorithm that summarises the consensus' core messages.ResultsA multimodal intervention strategy is the mainstay of OA management and the choice of any single or multimodal intervention may vary over the course of the disease. Overall, a non-pharmacological core treatment set of patient education, weight loss and exercise is recommended for all patients. When pharmacotherapy is indicated, symptomatic slow-acting drugs for osteoarthritis are recommended at the early stage of disease, and they can be paired with physical therapy as background treatment. Concurrent advanced pharmacotherapy that includes non-steroidal anti-inflammatory drugs, intraarticular injections and short-term weak opioids can be considered if patients do not respond sufficiently to background treatment. Patients with severe symptomatic knee OA should be considered for knee replacement surgery. Management should begin with specific treatments with the least systemic exposure or toxicity, and the choice of treatment should be determined as a shared decision between patients and their team of healthcare providers.ConclusionsThis consensus presents nine recommendations that advocate an algorithmic approach in the management of patients living with knee OA. They are applicable to patients receiving treatment from primary to tertiary care providers in Malaysia as well as other countries.